KESALAHAN PENGGUNAAN TANDA BACA PADA KARANGAN NARASI SISWA KELAS X IIS-A SMA SWASTA KAMPUS TELUKDALAM TAHUN PEMBELAJARAN 2020/2021 - Siriakus Amajihono (Universitas Nias Raya, 2022)
The problem in this research is the error in using punctuation marks in the narrative essays ofclass X IIS-A private students at Teluk Campus in the 2020/2021 academic year which is still not fully in accordance with the general Indonesian spelling guidelines (PUEBI) describe errors in the use of.punctuation marks in students' narrative essays.this research approach is a qualitative research with descriptive type.the data source in this study is the result of narrative essays by class X IIS-A students at private high school, Teluk Campus in the 2020/2021 academic yearThe results of this study show that the use of punctuation errors in students' narrative essays is 143 errors, and the use of correct.punctuation marks is 99 punctuation marks.the total number of punctuation marks used is 242 punctuation marks. The use of a comma is 69 errors. Then, errors in the use of periods in student narrative essays that were found by researchers were 34 errors. .furthermore, errors in the use of hyphens that were found by researchers in student narrative essays were 15 errors Next, the errors in using exclamation marks that the researchers found were 14 errors. .furthermore, the errors in using quotation marks that the researchers found were 8 errors..based on the results of the study, it can be concluded that in writing narrative essays students make mistakes due to lack of mastery of the use of punctuation marks, limited vocabulary and students'.inaccuracy in writing narrative essays to teach students about the use of punctuation in narrative essays and expand students' vocabulary. (2) for students, they should expand their vocabulary, in order to produce good and correct writing